Fluoride removal from water by adsorption on china clay - Chaturvedi A.K.; Pathak K.C.; Singh V.N. (My University, 2025)
China clay has been used as adsorbent for removal of fluoride from water at different concentrations, temperatures and pH. Kinetics of adsorption as well as adsorption isotherms at different temperatures for the present system have been investigated. Fluoride removal is favoured by low concentration, high temperature and acidic pH. The alumina constituent of china clay is responsible for maximum adsorption of fluoride in the pH range of interest. © 1988.